Metacognitive strategies and levels of reading comprehension in students of the 4th grade of primary school of the educational institution "Inka Pachacutec N ° 6037 of the district of San Juan de Miraflores, 2018 - Ricra Purca, Melba Paulina (2020)
One of the most relevant research focuses on educational matters is contributed by learning strategies, which serve as tools to facilitate the acquisition, development, and implementation of content acquisition processes, making effective learning possible . The research had as a general problem: What relationship exists between metacognitive strategies and reading comprehension in the students of the Fourth Grade of Primary Education of the Educational Institution "Inka Pachacútec" No. 6037 of the District of San Juan de Miraflores UGEL 01? The objective of the research was to determine if there is a relationship between metacognitive strategies and levels of reading comprehension in students with difficulties in the area of ??comprehensive communication in the 4th grade of primary school of the Educational Institution "Inka Pachacútec" No. 6037 of the District of San Juan from Miraflores UGEL 01. It is a scientific investigation with a quantitative approach, with a correlational descriptive design. The data collection instruments were an inventory of metacognitive strategies and the reading comprehension test. The study population was 118 students from the “Inka Pachacútec” Educational Institution No. 6037 of the San Juan de Miraflores District UGEL 01. The representative sample was 118 students from the comprehensive communication area of the 4th A, 4th B, 4th C and 4th D. 15.3% have a low level of metacognition, 39.8 low, 39.8% regular and 5.1% high. 4.2% is deficient in Reading Comprehension Levels, 46.6% low, 43.2% regular, while 5.9% high. The following conclusion was reached: The metacognitive strategies are not related to the levels of reading comprehension, in students with difficulties in the area of comprehensive communication of the 4th grade of primary of the Educational Institution “Inka Pachacútec n ° 6037 of the District of San Juan de Miraflores, 2018 with a Spearman's rho r = 0.706 and a significance p = 0 (p <0.05) having 70.6% being high.